Effect of Rhizobium inoculation and phosphorus on growth and nitrogen fixation in tree legumes grown on highland vertisols - Luyindula, N.; Haque, I. (Wiley, 1992)
Two greenhouse experiments were conducted to investigate the effect of phosphorus application and Rhizobium inoculation on the growth and nitrogen fixation of three tree legume species on a highland vertisol. The first experiment involved Sesbania sesban and S. goetzei, the second Leucaena paniculata and L. leucocephala, both with varying levels of nitrogen applied. Growth and dry-matter production were assessed at 3 months after planting. Uninoculated Sesbania and Leucaena plants and inoculated plants without phosphorus showed poor growth compared to the treatment involving both inoculation and phosphorus application. Uninoculated Sesbania species had no nodules, while the Leucaena species nodulated slightly. In the inoculation and phosphorus application treatment, nodulation was abundant. Similar trends were observed for shoot nitrogen yield. The results of the experiments suggest that, to ensure early growth and good nitrogen fixation, both Rhizobium inoculation and phosphorus application are needed.